Caracterización de las conductas violentas y dinámica familiar en hombres con trastornos por consumo de sustancias - Cañadas, Francisco X. (2020)
Addiction to substance use is a problem of global relevance, it affects multiple areas of the human being, harming social, labor, academic and family. It is worrying that the rate of consumption is increasing and the start is presented at increasingly younger ages. In the world there was until 2016, around 275 million people in ages between 15 and 64 years old, who maintained a frequent consumption of some substance (UNODC, 2018). With regard to our region, in addition to the alarming data on the amount of people who consume, highlights the appearance of new substances psychoactive and the difficult understanding towards any tendency in the use of drugs in the entire hemisphere due to the lack of a consistent pattern. In Ecuador, the data is not less relevant, since a study carried out in 2016 with high school students, determined that 12.65% of adolescents accept the consumption of illicit drugs, of that percentage 39% consumed more than one substance, being the age of initiation of consumption 14 years (OAS, 2019).